Recovered granular sludge extracellular polymeric substances as carrier for bioaugmentation of granular sludge reactor - Oliveira, Ana S. (2021)
An increasing amount of industrial chemicals are being released into wastewater collection systems and indigenous microbial communities in treatment plants are not always effective for their removal. In this work, extracellular polymeric substances (EPS) recovered from aerobic granular sludge (AGS) were used as a natural carrier to immobilize a specific microbial strain, Rhodococcus sp. FP1, able to degrade 2-fluorophenol (2-FP). The produced EPS granules exhibited a 2-FP degrading ability of 100% in batch assays, retaining their original activity after up to 2-months storage. Furthermore, EPS granules were added to an AGS reactor intermittently fed with saline wastewater containing 2-FP. Degradation of 2-FP and stoichiometric fluorine release occurred 8 and 35 days after bioaugmentation, respectively. Chemical oxygen demand removal was not significantly impaired by 2-FP or salinity loads. Nutrients removal was impaired by 2-FP load, but after bioaugmentation, the phosphate and ammonium removal efficiency improved from 14 to 46% and from 25 to 42%, respectively. After 2-FP feeding ceased, at low/moderate salinity (0.6–6.0 g L−1 NaCl), ammonium removal was completely restored, and phosphate removal efficiency increased. After bioaugmentation, 11 bacteria isolated from AGS were able to degrade 2-FP, indicating that horizontal gene transfer could have occurred in the reactor. The improvement of bioreactor performance after bioaugmentation with EPS immobilized bacteria and the maintenance of cell viability through storage are the main advantages of the use of this natural microbial carrier for bioaugmentation, which can benefit wastewater treatment processes.